Effects of social tourism on unemployed individuals’ self-efficacy and job-search behaviour - Kakoudakis, Konstantinos (2014)
Findings from social tourism research on low-income groups have shown that social tourism holds several psychological benefits for participants (e.g. Minnaert, Maitland, and Miller, 2009; McCabe and Johnson, 2013). On the other hand, the evidence base about any direct linkages between these individual benefits, and social and economic benefits, remains weak, affecting the promotion of social tourism in the UK policy agenda. In line with the recent debate on social tourism in the country (see All-Party Parliamentary Group on Social Tourism, 2011), the current socioeconomic trends, and more specifically the high rates of general and long-term unemployment (Eurostat, 2013; ONS, 2013b), and the consequences of unemployment for individuals, their families, and the society, this study sets to explore whether social tourism holds any particular psychological benefits for unemployed individuals in Great Britain, and the extent to which, such benefits have, in turn, positive effects on their job-search behaviour (JSB). Drawing upon findings from social tourism studies on low-income groups, psychology studies on unemployment and job-search behaviour, and social psychology theories with specific reference to Bandura’s (1986, 1997) social cognitive theory, this study examines the psychological benefits of tourism participation within the context of self-efficacy beliefs. Self-efficacy (SE) is the main construct of social cognitive theory, and it has been found to play a central role in unemployed individuals’ JSB. Utilising a mixed methods approach to data collection and analysis, the study incorporates a pre- post-test non-experimental design (n=57) and semi-structured interviews (n=13), with the aim to investigate any such effects over time, and to understand how they are manifested. Access to the rare target population, became possible through the database of the Family Holiday Association, the main provider of social tourism for low-income families in the UK.